IMPLEMENTATION OF PROJECT BASED LEARNING MODEL TO IMPROVE STUDENTS' CREATIVE THINKING SKILLS IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS: CASE STUDY AT SMP DARUL IKHSAN BOARDING SCHOOL PEKALONGAN - Ryan Deriansyah (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' spiritual and moral values, particularly at the junior high school level. However, textual learning often hinders students' creative thinking abilities. This study aims to explore the application of the Project Based Learning (PjBL) method in PAI at SMP Darul Ikhsan Pekalongan, focusing on enhancing students' creative thinking skills and learning outcomes. This research employed Classroom Action Research (CAR) involving 30 eighth-grade students. Data were collected through interviews, observations, and written tests. During the pre-cycle phase, initial conditions were identified through observation and interviews. In Cycle 1, students created posters about noble character values using design applications. In Cycle 2, students developed videos of the stories of Prophet Muhammad SAW, which were uploaded to YouTube. The results showed a significant increase in students' creative thinking skills, from 30% in the pre-cycle to 70% in Cycle 1 and 90% in Cycle 2. The average learning outcomes also improved from 40 (pre-cycle) to 70 (Cycle 1) and 90 (Cycle 2), with a mastery level of 80%. The project activities encouraged students to deeply understand the material, appreciate Islamic values, and apply them in daily life. This study demonstrates that PjBL effectively enhances student engagement and provides meaningful learning experiences. It is recommended that this method be consistently integrated into PAI learning to foster students' creativity and comprehension sustainably